PENGARUH KOMPETENSI GURU TERHADAP KARAKTER SISWA PADA LINGKUNGAN DI SD ISLAM ATHIRAH BUKIT BARUGA MAKASSAR - Aminah Aminah; Fatmawati Fatmawati; Yermi Yermi; Musdalifah Syamsul (UNM Environmental Journals, 2022)
This study aims to determine the effect of teacher competence on student character in the environment at SD Islam Athirah Bukit Baruga Makassar. This type of research is a survey. Data was collected using a questionnaire. The sample in the study was 42 people. The data were analyzed using descriptive and inferential analysis. The results of the analysis show that: (1) teacher competence in managing learning and student character in the environment at SD Islam Athirah Bukit Baruga Makassar is in the high category, and (2) there is a positive influence of teacher competence on student character in the environment at SD Islam Athirah Bukit Baruga Makassar, with a regression coefficient of 0.867 means that if teacher competence is increased it will have a positive effect on student character in the environment of 0.867 of the magnitude of the increase in teacher competence.